Sprawdziany testowe z matematyki - sposób na głębsze zrozumienie i utrwalenie wykładanego materiału - Jóźwikowska, Alina; Tempczyk, Wacława (Mathematical Test Exercises - a Method to Understand Deeper and Consolidate Knowledge, 2006)
Mathematics in economics studies is not a principle subject, however it is the basis of many occupational subjects. In teaching mathematics the major attention is put on the understanding of the definitions and theorems and the ability of their practical use. As a result of the small amount of time provided for mathematical subjects, the main accent is put on practical aspects, not on theory. This often results in partial understanding of presented material, especially because students usually learn only these facts that were discussed in exercise. What is more, due to their high school experience, they are accustomed to assimilate computing schemas, without understanding the essence of the matter. To change this, and to force students to have a wider look at the subject, we introduced, apart form solving ordinary problems, tests in our classes. While preparing test exercises, we concentrated on three main purposes. Our intention was to check:1) the understanding of the definitions,2) the familiarity with main theorems and relations between discussed conceptions,3) the ability of combing facts and proper concluding.In the article some examples of the tests solved by first year students of Agricultural University are presented. They concern linear algebra and differential and integral calculus of one and many variables. By comparing the results of tests and computational problems we made an effort to draw conclusions how to teach more effectively.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 58-68